2019
DOI: 10.1128/aac.02310-18
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cytological Profiling as a Tool To Study Mechanisms of Action of Antibiotics That Are Active against Acinetobacter baumannii

Abstract: An increasing number of multidrug-resistant Acinetobacter baumannii (MDR-AB) infections have been reported worldwide, posing a threat to public health. The establishment of methods to elucidate the mechanism of action (MOA) of A. baumannii-specific antibiotics is needed to develop novel antimicrobial therapeutics with activity against MDR-AB. We previously developed bacterial cytological profiling (BCP) to understand the MOA of compounds in Escherichia coli and Bacillus subtilis. Given how distantly related A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 76 publications
4
54
0
Order By: Relevance
“…Ciprofloxacin, rifampicin, and tetracycline were used as inhibitors to replication, transcription, and translation respectively. Fluorescence microscopy results of VP AHPND treated with antibiotics showed that each antibiotic treatment led to a unique morphological change in VP AHPND , similar to what previously observed in gram-negative Escherichia coli and Acinetobactor baumannii treatments 31,42 . Upon ciprofloxacin treatment, inhibition of DNA replication resulted in cell elongation and DNA pooling at the midcell while treatment with rifampicin resulted in DNA decondensation ( Fig.…”
Section: Phage Seahorse Infection Triggers the Condensation Of Host Nsupporting
confidence: 82%
See 2 more Smart Citations
“…Ciprofloxacin, rifampicin, and tetracycline were used as inhibitors to replication, transcription, and translation respectively. Fluorescence microscopy results of VP AHPND treated with antibiotics showed that each antibiotic treatment led to a unique morphological change in VP AHPND , similar to what previously observed in gram-negative Escherichia coli and Acinetobactor baumannii treatments 31,42 . Upon ciprofloxacin treatment, inhibition of DNA replication resulted in cell elongation and DNA pooling at the midcell while treatment with rifampicin resulted in DNA decondensation ( Fig.…”
Section: Phage Seahorse Infection Triggers the Condensation Of Host Nsupporting
confidence: 82%
“…3a). The archetypal DNA shape of protein translation inhibition in many studies is a "toroid" 31,42,43 , but DNA shape alteration during very early translation inhibition by an antibiotic (less than one hour) has never been reported. Thus, time-course analysis of toroidal DNA formation in VP AHPND during tetracycline treatment was performed.…”
Section: Phage Seahorse Infection Triggers the Condensation Of Host Nmentioning
confidence: 99%
See 1 more Smart Citation
“…We next asked whether drug treatment of Mtb, like M. smegmatis , elicited well-defined cytological fingerprints. Guided by cytological profiling methods in other bacterial species (79), we treated Mtb grown in standard rich growth medium with a high drug dose (3x the 90% inhibitory concentration; IC90) for 17 hours (~1 doubling time). We generated a dataset of morphological features from Mtb treated with 34 antibacterials that encompass a wide range of drug classes and classified the target pathway of each drug according to published findings (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In other bacterial systems such as Escherichia coli , Bacillus subtilis , and Acinetobacter baumannii , profiling of cytological changes in response to treatment has yielded a rapid and resource-sparing procedure to determine drug mechanism (79). This method, known as bacterial cytological profiling (BCP), groups drugs with similar mechanisms of action by clustering profiles of drug-treated bacteria using multivariate analysis methods such as principal component analysis (PCA) (79). BCP is efficient and rapid because these cytological features can be automatically derived from high-throughput images of stained, fixed samples.…”
Section: Introductionmentioning
confidence: 99%